Community collaboration: sharing responsibility, not power - Merriman, Tim, speaker (Colorado State University. Libraries, 2012)
Expecting people to share power and collaborate is often unrealistic in community and agency settings. The HEART approach to collaborative planning brings groups into collaboration to share responsibilities and a planning approach with the understanding that their power and ethical framework is not compromised. Examples will be shared from national and international settings that demonstrate what can be achieved when collaboration does not threaten the core values of participating groups and agencies.
Community collaboration: sharing responsibility, not power: an ethical approach
Presented at the Fall 2012 Center for Collaborative Conservation (https://collaborativeconservation.org/) Seminar and Discussion Series, "Power and Ethics in (Collaborative) Conservation", September 11, 2012, Colorado State University, Fort Collins, Colorado. This series focused on the work that the CCC's Collaborative Conservation Fellows have been doing across the Western U.S. and around the world.
Tim Merriman has a BS in zoology, secondary teaching certificate, MA in aquatic ecology and a PhD in speech from Southern Illinois University (SIU). He has served as Executive Director of National Association for Interpretation (NAI) for the past 18 years and now consults with Lisa Brochu, as Heartfelt Associates. During his 42-year career, Merriman has traveled in 22 nations around the world to train interpretive planners and trainers. He co-authored with Lisa Brochu Personal Interpretation: Connecting your audience to heritage resources (2002, 2007), Management of Interpretive Sites (2005), History of Heritage Interpretation in the United States (2006) and Put the Heart Back in Your Community (2011).
Includes recorded speech and PowerPoint presentation.
Accessibility features: Unedited transcript.
Keywords: community indicators; sustainability; collaborative planning; balance; stakeholders; rules of engagement